Downstream developments of a traditional industry through foreign investment and local knowledge and capabilities – evidence from the Sri Lankan rubber industry. (1st January 2011) - Nakandala, Dilupa; Turpin, Tim
This article analyses the Sri Lankan rubber industry in terms of the integration of local knowledge and capabilities with technology and skills derived from foreign direct investment. We argue that foreign technology initiated a transformational process within the rubber products sector but functional upgrading of the traditional industry from raw rubber production to value-added rubber products manufacturing was underpinned by a symbiotic relationship between a strong public innovation system in the upstream value chain that enhanced absorptive capacity in the rubber production industry, enabling subsequent spillover to the local industry, and increased innovation capabilities among local partner firms in rubber products manufacturing. The findings of this study inform the policymakers of the importance of designing heterogeneous policies across sectors.